POLA KOMUNIKASI PENCARI SUAKA ASAL AFGHANISTAN DALAM BERINTERAKSI DI RUMAH DETENSI IMIGRASI PEKANBARU - Try Panji Akbari; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The movement of people from one place to another is a common thing in today's times. Technology support and access to adequate transportation as well as the interests of the individual is the reason for the transfer to happen. Turbulent political conditions and trigger wars in some countries is one of the reasons for the immigration of people for seek asylum. Pekanbaru city is one of the cities that is much visited by immigrants with a reason to seeking asylum. Until September 2015 there were 300 people from different countries who inhabit the immigration detention center and of the number of 300 asylum seekers from Afghanistan were the most with 217 asylum seekers. they have to make any interactions with the other asylum seekers or the immigrants officers. The goal of this research is to analyze the communication patterns and to identify the verbal and nonverbal communication of the Afghanistan asylum seekers in the Immigration Detention Of Pekanbaru.This research used descriptive qualitative research metode, with the selection of informants using purposive sampling technique, which selects three informants, which is a KASUBSI Security of Immigration Detention Pekanbaru, and two Afghanistan asylum seekers. The data collection techniques are used observation, in-depth interviews, and documentation.While,for the data analysis was refer to the interactive model of Huberman and Miles. Then, for checking the validity of data were using extension participation and triangulation techniques.The results of this research are showed that the communication patterns of the Afghanistan asylum seekers are divided into two; the first one is internalcommunication pattern which uses all channels outline. In this pattern, they can make any interaction and it will influence each other. And then In this pattern of communication with external groups, the leader will come out of the loop all channels outline and served as a translator for the group members and external groups. In daily interaction, they use verbal communication in Parcy language or English with nonverbal communication such as facial, gestural, and postural message.Keyword: Communication pettern, Afghanistan Seekers Asylum, Immigration Detention of Pekanbaru